The twilight children - Hernandez, Gilbert (DC Comics, 2016)
"For the first time ever, legendary comics creators Gilbert Hernandez (Love and Rockets) and Darwyn Cooke (DC: THE NEW FRONTIER) have joined forces for a surreal project unlike anything you've ever read before! When a white orb washes up on the shore of a remote Latin American village, a group of children naturally poke at the strange object to see what it is. The orb explodes, leaving the children completely blind. And when a beautiful young woman who may be an alien is found wandering the seafront, she's taken in by the townspeople, but soon becomes a person of interest to a quirky pair of undercover CIA agents, and the target of affection for a young scientist. Can they come together to prevent an all-out alien invasion and save the souls in this sleepy, seaside town? Collects THE TWILIGHT CHILDREN #1-4 of the four-issue miniseries"--